Remote radio control of insect flight - Sato, Hirotaka; Berry, Christopher W.; Peeri, Yoav; Baghoomian, Emen; Casey, Brendan E.; Lavella, Gabriel; VandenBrooks, John M.; Harrison, Jon; Maharbiz, Michel M. (Frontiers in Integrative Neuroscience, 2009)
We demonstrated the remote control of insects in free flight via an implantable radio-equipped miniature neural stimulating system. The pronotum mounted system consisted of neural stimulators, muscular stimulators, a radio transceiver-equipped microcontroller and a microbattery. Flight initiation, cessation and elevation control were accomplished through neural stimulus of the brain which elicited, suppressed or modulated wing oscillation. Turns were triggered through the direct muscular stimulus of either of the basalar muscles. We characterized the response times, success rates, and free-flight trajectories elicited by our neural control systems in remotely-controlled beetles. We believe this type of technology will open the door to in-flight perturbation and recording of insect flight responses.